Bhagavāna tāruṃ śuṃ thaśe - Ācārya, Guṇavantarāya (Gūrjara Grantharatna Kāryālaya, 2010)
Tahomatanāmuṃ – Adālatī tapāsa – Bhagavāna āvyo Stories based on suspense theme; for juvenile
Reprint. Originally published: 1956. - Short stories. - Gujarati in Gujarati-Schr
Keywords: Gujarātī-Sprache; Kurzgeschichte; Geschichte 1900-2000